Air filtration improvement of konjac glucomannan-based aerogel air filters through physical structure design. (3rd March 2021) - Qian, Hong; Fang, Ying; Wu, Kao; Wang, Hao; Li, Bin; Jiang, Fatang
Abstract: This study presents two methods to improve the air filtration performance of konjac glucomannan (KGM)-based aerogel air filters through physical structure design by changing the pore-size distribution and the surface area, using an air purifier. Results indicated that KGM-based aerogels had a comparable filtration effect with the commercial air filter with a longer purification time. This purification time could be shortened by over 50%, by changing the pore-size distribution from large size to small size or increase the surface area with the fold structure. This should boost the development of polysaccharide-based aerogel used as the air filter.